DoFun 3.0: functional equations in mathematica - Huber, Markus Q.; Cyrol, Anton Konrad; Pawlowski, Jan M. (Computer physics communications, 2020)
We present version 3.0 of the Mathematica package DoFun for the derivation of functional equations. In this version, the derivation of equations for correlation functions of composite operators was added. In the update, the general workflow was slightly modified taking into account experience with the previous version. In addition, various tools were included to improve the usage experience and the code was partially restructured for easier maintenance. - Program summary - Program Title: DoFun Program Files doi: http://dx.doi.org/10.17632/y7rwzywr6w.1 Licensing provisions: GPLv3 Programming language: Mathematica, developed in version 11.3 Nature of problem: Derivation of functional renormalization group equations, Dyson-Schwinger equations and equations for correlations functions of composite operators in symbolic form which can be translated into algebraic forms. Solution method: Implementation of algorithms for the derivations of these equations and tools to transform the symbolic to the algebraic form. Unusual features: The results can be plotted as Feynman diagrams in Mathematica. The output is compatible with the syntax of many other programs and is therefore suitable for further (algebraic) computations.
Available online: 05 November 2019
Gesehen am 07.10.2022